Diversity and Community Structure of Ants (Formicidae) in Residential Ecosystems - Indrawan Indrawan; Muhammad Rizaldi Trias Jaya Putra Nurdin; Ariandi Ariandi (Indonesian Journal of Ecology and Conservation, 2024)
Ants (Formicidae) are a group of insects that play an important role in maintaining ecosystem balance and are often used as bioindicators of environmental conditions. However, information on ant diversity in residential ecosystems in West Sulawesi remains limited. This study aimed to analyze the diversity and community structure of ants and their relationship with environmental parameters in residential ecosystems in Labuang Parabaya Hamlet, Onang Village, Majene Regency. Sampling was conducted using pitfall traps and hand collecting methods in two habitat types, namely household gardens and residential surroundings. Data were analyzed using the Shannon–Wiener diversity index (H’), evenness index (E), dominance index (C), and correlation analysis with environmental parameters. The results showed that the ant community consisted of four species with a total of 106 individuals, with Solenopsis invicta being the most abundant species. The diversity index was categorized as moderate (H’ = 1.16), with high evenness (E = 0.84) and low dominance (C = 0.34). Among the environmental parameters measured, soil pH and air humidity showed the strongest influence on ant diversity, whereas light intensity had a relatively lower effect. These findings indicate that the structure of ant communities in residential ecosystems is influenced by habitat conditions and environmental factors.